Pragmatic, feasibility randomized controlled trial of a recorded mental health recovery narrative intervention: narrative experiences online intervention for informal carers (NEON-C) - Ng, Fiona; Rennick-Egglestone, Stefan; Onwumere, Juliana; Newby, Christopher; Llewellyn-Beardsley, Joy; Yeo, Caroline; Ali, Yasmin; Pollock, Kristian; Kotera, Yasuhiro; Pomberth, Scott; Gavan, Sean P.; van der Krieke, Lian; et al. (Frontiers in Psychiatry, 2024)
Informal carers of people with mental health problems often have unmet support needs. Mental health recovery narratives are increasingly accessible but their relevance to, and impact on informal carers has been minimally investigated. The Narrative Experiences Online (NEON) Intervention is a first-in-field intervention which provides informal carers with access to a diverse collection of recorded mental health recovery narratives. The aim of this trial was to examine the feasibility and acceptability of the NEON Intervention on informal carers.Two-arm feasibility randomised controlled trial. Carers were randomly assigned to receiving versus not receiving the NEON Intervention. Feasibility aspects investigated included: the acceptability of the intervention and of randomisation, trial processes, engagement rates, recruitment procedures, attrition, sample size estimation, identification of candidate primary and secondary outcomes, and the feasibility to conduct a definitive trial. Qualitative process evaluation was conducted. Findings 121 carers were eligible, 54 carers were randomised (intervention: 27, control: 27). Twelvemonth follow-up data was available for 36 carers. Carers accessed a mean of 25 narratives over a 12-month period and the intervention group, compared with the control group, reported a small effect on hope, and a moderate effect on the presence of meaning in life. Five modifications were recommended to improve the user experience, applicability, and trial processes.The NEON Intervention is feasible and acceptable. Significant refinement of the NEON Intervention and trial processes is required to personalise and ensure applicability to carers. Further feasibility testing is recommended prior to a definitive trial.